2004
DOI: 10.1159/000079947
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence in Multiple Sclerosis: A 35-Year Follow-Up

Abstract: The risk of cancer among multiple sclerosis (MS) patients was evaluated emphasising cancers with a potentially infectious aetiology. Cancer incidence was estimated among incident MS patients in 1964–1993 (n = 1,597) in Finland. The cohort was followed up for cancer incidence through the Finnish Cancer Registry until 1999. A total of 85 cancer cases were diagnosed showing a standardised incidence ratio (SIR) of 1.0 (95% CI 0.8–1.2) for all cancers. The risk (SIR) of haematological tumours was 1.1 and that of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
39
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 22 publications
9
39
1
Order By: Relevance
“…An alternative explanation for the overall null result is a possible underrepresentation of RA patients with severe disease and presumably higher risk of lymphoma 38 through selfselection in case-control studies as opposed to in registry-based cohort studies. 10 Inflammatory bowel disorders, type 1 diabetes, sarcoidosis, pernicious anemia, and multiple sclerosis were not associated with risk of NHL overall, consistent with the majority of previous reports, 14,30,[40][41][42] and there was no strong evidence for subtypespecific associations. In Crohn's disease, a recent large metaanalysis 43 reported a moderately increased risk of lymphoma overall, but latency was not evaluated; therefore a possible risk inflation by initial misdiagnoses of lymphomas cannot be excluded.…”
Section: Autoimmune Disorders and Lymphoma Subtypes 4035supporting
confidence: 83%
“…An alternative explanation for the overall null result is a possible underrepresentation of RA patients with severe disease and presumably higher risk of lymphoma 38 through selfselection in case-control studies as opposed to in registry-based cohort studies. 10 Inflammatory bowel disorders, type 1 diabetes, sarcoidosis, pernicious anemia, and multiple sclerosis were not associated with risk of NHL overall, consistent with the majority of previous reports, 14,30,[40][41][42] and there was no strong evidence for subtypespecific associations. In Crohn's disease, a recent large metaanalysis 43 reported a moderately increased risk of lymphoma overall, but latency was not evaluated; therefore a possible risk inflation by initial misdiagnoses of lymphomas cannot be excluded.…”
Section: Autoimmune Disorders and Lymphoma Subtypes 4035supporting
confidence: 83%
“…Exclusion of irrelevant references and/or duplicates left 204 potential full-text articles. Fifty-one articles [3,7,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71] (with a total of 577,013 participants) fulfilled our inclusion criteria (fig. 1) and were included in the qualitative data synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [32,36,37,38,39,40,41,42] on 54,929 patients with MS reflected a reduced incidence of cancer in general (ES = 0.91; 95% CI: 0.87-0.95; I 2 = 30.3%), with low between-study heterogeneity (Q statistic: p = 0.19; fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, there was no significantly increased risk beyond the first year of follow-up; thus, the positive association could be due to misclassification. In multiple sclerosis, studies have consistently shown no excess risk of lymphoma or hematopoietic malignancy (113)(114)(115). Associations between diabetes mellitus and malignant lymphomas have been described occasionally (116), but the overall picture is that of no association (117,118).…”
Section: Autoimmune/inflammatory Conditions Linked To Lymphomamentioning
confidence: 99%